Insights into structure and dynamics of (Mn, Fe)Ox-promoted Rh nanoparticles. (29th May 2018) - Dimitrakopoulou, Maria; Huang, Xing; Kröhnert, Jutta; Teschner, Detre; Praetz, Sebastian; Schlesiger, Christopher; Malzer, Wolfgang; Janke, Christiane; Schwab, Ekkehard; Rosowski, Frank; Kaiser, Harry; Schunk, Stephan; et al.
Abstract : The mutual interaction between Rh nanoparticles and manganese/iron oxide promoters in silica-supported Rh catalysts for the hydrogenation of CO to higher alcohols was analyzed by applying a combination of spectroscopy and microscopy. Abstract : The mutual interaction between Rh nanoparticles and manganese/iron oxide promoters in silica-supported Rh catalysts for the hydrogenation of CO to higher alcohols was analyzed by applying a combination of integral techniques including temperature-programmed reduction (TPR), X-ray photoelectron spectroscopy (XPS), X-ray absorption spectroscopy (XAS) and Fourier transform infrared (FTIR) spectroscopy with local analysis by using high angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) in combination with energy dispersive X-ray spectroscopy (EDX). The promoted catalysts show reduced CO adsorption capacity as evidenced through FTIR spectroscopy, which is attributed to a perforated core–shell structure of the Rh nano-particles in accordance with the microstructural analysis from electron microscopy. Iron and manganese occur in low formal oxidation states between 2+ and zero in the reduced catalysts as shown by using TPR and XAS. Infrared spectroscopy measured in diffuse reflectance at reaction temperature and pressure indicates that partial coverage of the Rh particles is maintained at reaction temperature under operation and that the remaining accessible metal adsorption sites might be catalytically less relevant because the hydrogenation of adsorbed carbonyl species at 523 K and 30 bar hydrogen essentially failed. It is concluded that Rh 0 is poisoned due to the adsorption of CO under the reaction conditions of CO hydrogenation. The active sites are associated either with a (Mn, Fe)O x ( x < 0.25) phase or species at the interface between Rh and its co-catalyst (Mn, Fe)O x .